Delivery and use of individualised feedback in large class medical teaching - Burr, Steven A.; Brodier, Elizabeth; Wilkinson, Simon (BioMed Central, 2013)
Background: Formative feedback that encourages self-directed learning in large class medical teaching is difficult to deliver. This study describes a new method, blueprinted feedback, and explores learner’s responses to assess its appropriate use within medical science teaching. Methods: Mapping summative assessment items to their relevant learning objectives creates a blueprint which can be used on completion of the assessment to automatically create a list of objectives ranked by the attainment of the individual student. Two surveys targeted medical students in years 1, 2 and 3. The behaviour-based survey was released online several times, with 215 and 22 responses from year 2, and 187, 180 and 21 responses from year 3. The attitude-based survey was interviewer-administered and released once, with 22 responses from year 2 and 3, and 20 responses from year 1. Results: 88-96% of learners viewed the blueprinted feedback report, whilst 39% used the learning objectives to guide further learning. Females were significantly more likely to revisit learning objectives than males (p = 0.012). The most common reason for not continuing learning was a ‘hurdle mentality’ of focusing learning elsewhere once a module had been assessed. Conclusions: Blueprinted feedback contains the key characteristics required for effective feedback so that with further education and support concerning its use, it could become a highly useful tool for the individual and teacher.